2006
DOI: 10.3122/jabfm.19.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Family Physician's Knowledge, Beliefs, and Self-reported Practice Patterns Regarding Hyperlipidemia: A National Research Network (NRN) Survey

Abstract: Objective: Family physicians have the potential to make a major impact on reducing the burden of cardiovascular disease through the optimal assessment and management of hyperlipidemia. We were interested in assessing the knowledge, beliefs, and self-reported practice patterns of a representative sample of family physicians regarding the assessment and management of hyperlipidemia 2 years after the release of the evidence-based National Cholesterol Education Program (NCEP) Adult Treatment Panel (ATP) III guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 14 publications
(9 reference statements)
4
38
0
2
Order By: Relevance
“…30 In another study, elevated levels of LDL-C were found as well in 114 (74.0%) of 154 elderly men with ED. 31 In a retrospective study involving 988 men (aged 46-81 years), Eaton et al 32 found that men with poor to very poor erectile function had twice the odds of an elevated TC/HDL-C ratio (P=.02) compared with men with good and very good erectile function. Thus, aggressive treatment of both ED and dyslipidemia may result in a decrease in cardiovascular events and improvement in erectile function.…”
mentioning
confidence: 99%
“…30 In another study, elevated levels of LDL-C were found as well in 114 (74.0%) of 154 elderly men with ED. 31 In a retrospective study involving 988 men (aged 46-81 years), Eaton et al 32 found that men with poor to very poor erectile function had twice the odds of an elevated TC/HDL-C ratio (P=.02) compared with men with good and very good erectile function. Thus, aggressive treatment of both ED and dyslipidemia may result in a decrease in cardiovascular events and improvement in erectile function.…”
mentioning
confidence: 99%
“…(NCEP,2002) . That could justify the higher degree of screening that was found also in a previous study that the age at which family physicians begin screening lies between the ages recommended by the ATP III guidelines and the USPSTF (Eaton et al, 2006).…”
Section: Q28mentioning
confidence: 71%
“…[7][8][9][10][11][12][13][14] Potential barriers to the implementation of cholesterol guidelines into clinical practice appear related to clinician knowledge, attitudes, and behaviors; patient knowledge, attitudes, and behaviors; doctor-patient communication issues; and system-based issues, such as economics and the lack of organized systems of care around the recognition and treatment of hyperlipidemia. [15][16][17] Thus a multimodal approach affecting clinicians, patients, doctor-patient communication, and offi ce systems (clinical decision support tools, patient education materials, offi ce waiting room computer kiosks) is likely to be needed to translate these guidelines into clinical practice.…”
Section: Chol Es T Erol Guidel Ines In To Pr Ac T Icementioning
confidence: 99%